Estudio de mejora integral en la empresa de pastelería Claudia Cupcakes - Martínez Montalvo, Daniela (2015)
For the recent research, it was decided to make a study of comprehensive improvement of processes in the company Claudia Cupcakes EIRL, for which, taking into account the knowledge acquired throughout the career of Industrial Engineering, some improvements proposals were raised to the problems identified in the company, in order to contribute to their growth and development.